Motivasi Petani dalam UsahataniBawang Putih (Allium sativum) di Kecamatan Tawangmangu, Kabupaten Karanganyar - Udi Arga; Retno Setyawati; apja Anantayu (Balai Pelatihan Pertanian Jambi, 2021)
This study aims to analyze: (1) the motivation of farmers in garlic cultivation; (2) factors that influence farmer motivation; (3) the relationship between the factors that influence motivation and motivation of farmers in garlic crop farming. The basic method used is a quantitative method with survey techniques. The determination of the research location was carried out deliberately in Tawangmangu District, Karanganyar Regency. Sampling using proportional random sampling technique and respondents were taken as many as 50 farmers. Data analysis used the Spearman Rank Correlation Test ( ) with the IBM SPSS Statistics program. The results showed that: (1) social needs dominate the level of motivation of farmers in garlic farming; (2) motivating factors are age in the early elderly category, low formal education, high land area, very low income, very high experience, low social environment, low economic environment, high farmer group institutions, and low government / private support; (3) There is a very significant relationship between income, social, and economic factors with the motivation of farmers in garlic crop farming. There is a significant relationship between the factors of land area, farmer group institutions and government / private support with farmer motivation in garlic crop farming. There is no significant relationship between the factors of age, education and experience with the motivation of farmers in garlic crop farming in Tawangmangu District, Karanganyar Regency.